Overcoming Depression: Stories of Terminated Employees amidst COVID-19 - Adlit, Marlon F.; Ida, Irish Mae A. (Future Science / FSH-PH Publications, 2022)
COVID-19 virus caused drastic changes in people's lives, especially in terms of employment. Employees were greatly impacted by this pandemic, as there were terminated from their jobs. This study investigated how depression affects terminated workers and how they manage it throughout the pandemic. A qualitative design was employed to perform this study. A structured type of interview was conducted on five samples using an online platform. To establish the number of samples required for the investigation, convenience sampling was used. The data was analyzed in-depth using a narrative technique, which resulted in the study's findings and conclusions. Five (5) terminated employees such as professional photographer, construction worker, hairdresser, driver, and varsity coach were among the participants. The participants in this study were found to experience depression due to family financial issues caused by the loss of a job during the pandemic. Participants reported feelings of sadness and loneliness, as well as inability to think, low self-esteem, insomnia and hypersomnia, a lack of ambition to accomplish anything, and suicidal or negative thoughts. Accordingly, through their families' emotional support, the participants have been able to overcome their depression.